Postnatal expression of Cat-315-positive perineuronal nets in the SAMP10 mouse primary somatosensory cortex - Hiroshi Ueno; Yu Takahashi; Sachiko Mori; Eriko Kitano; Shinji Murakami; Kenta Wani; Yosuke Matsumoto; Motoi Okamoto; Takeshi Ishihara (IBRO Neuroscience Reports)
Perineuronal nets (PNNs) form at the end of the critical period of plasticity in the mouse primary somatosensory cortex. PNNs are said to have functions that control neuroplasticity and provide neuroprotection. However, it is not clear which molecules in PNNs have these functions. We have previously reported that Cat-315-positive molecules were not expressed in the PNNs of the senescence-accelerated model (SAM)P10 strain model mice at 12 months of age. To confirm whether the loss of Cat-315-positive molecules occurred early in life in SAMP10 mice, we examined Cat-315-positive PNNs in the primary somatosensory cortex during postnatal development. This research helps to elucidate the function of PNNs and the mechanism of cognitive decline associated with ageing. To confirm whether Cat-315-positive PNNs changed in an age-dependent manner in SAMP10 mice, we examined the primary somatosensory cortex at 21, 28, and 56 days after birth. We compared these results with those of senescence-accelerated mouse-resistant (SAMR) mice. In SAMP10 mice, Cat-315-positive PNNs were expressed in the primary somatosensory cortex early after birth, but their expression was significantly lower than that in SAMR1 mice. Many other molecules that calibrated the PNN were unchanged between SAMP10 and SAMR1 mice. This study revealed that the expression of the Cat-315 epitope was decreased in the primary somatosensory cortex of SAMP10 mice during postnatal development. SAMP10 mice have had histological abnormalities in their brains since early life. Furthermore, using SAMP10 will be useful in elucidating the mechanism of age-related abnormalities in brain function as well as in elucidating the function and structure of PNNs.